(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
This research investigates the potential of natural and synthetic fibres on flexural strength of foamcrete mortar. The are 7 different types of fibres had been used such as pulverized fuel ash, wood ash, silica fume, palm oil fuel ash, polypropylene fibre, coconut fibre and steel fibre. These natural and synthetic additives have different abilities that contribute positive outcomes to the properties of foamcrete mortar. Pozzolanic materials and fibres were used as additives to be included with control foamcrete mortar mixtures in order to enhance its flexural properties. From the overall analysis, it has been confirmed that coir fibre recorded the highest flexural strength in 7 days compared to other additives and the control sample. Coir fibre of 0.4% reached highest strength in 180 days without allowing other additives to overcome its overall flexural strength. It should be pointed out that, the more the addition of fibres in the base mix, the higher the strength obtained due to its low cellulose content.